Protective ventilation during anaesthesia reduces major postoperative complications after lung cancer surgery: A double-blind randomised controlled trial. Issue 10 (October 2018) - Marret, Emmanuel; Cinotti, Raphael; Berard, Laurence; Piriou, Vincent; Jobard, Jacques; Barrucand, Benoit; Radu, Dragos; Jaber, Samir; Bonnet, Francis
Abstract : BACKGROUND: Thoracic surgery for lung resection is associated with a high incidence of postoperative pulmonary complications. Controlled ventilation with a large tidal volume has been documented to be a risk factor for postoperative respiratory complications after major abdominal surgery, whereas the use of low tidal volumes and positive end-expiratory pressure (PEEP) has a protective effect. OBJECTIVE: To evaluate the effects of ventilation with low tidal volume and PEEP on major complications after thoracic surgery. DESIGN: A double-blind, randomised controlled study. SETTING: A multicentre trial from December 2008 to October 2011. PATIENTS: A total of 346 patients undergoing lobectomy or pneumonectomy for lung cancer. MAIN OUTCOME MEASURES: The primary outcome was the occurrence of major postoperative complications (pneumonia, acute lung injury, acute respiratory distress syndrome, pulmonary embolism, shock, myocardial infarction or death) within 30 days after surgery. INTERVENTIONS: Patients were randomly assigned to receive either lung-protective ventilation (LPV group) [tidal volume 5 ml kg −1 ideal body weight + PEEP between 5 and 8 cmH2 O] or nonprotective ventilation (control group) (tidal volume 10 ml kg −1 ideal body weight without PEEP) during anaesthesia. RESULTS: The trial was stopped prematurely because of an insufficient inclusion rate. Major postoperative complications occurred in 23/172 patients in the LPV group (13.4%) vs. 38/171 (22.2%) in the control group (odds ratio 0.54, 95% confidence interval, 0.31 to 0.95, P  = 0.03). The incidence of other complications (supraventricular cardiac arrhythmia, bronchial obstruction, pulmonary atelectasis, hypercapnia, bronchial fistula and persistent air leak) was also lower in the LPV group (37.2 vs. 49.4%, odds ratio 0.60, 95% confidence interval, 0.39 to 0.92, P  = 0.02).The duration of hospital stay was shorter in the LPV group, 11 [interquartile range, 9 to 15] days vs. 12 [9 to 16] days, P  = 0.048. CONCLUSION: Compared with high tidal volume and no PEEP, LPV combining low tidal volume and PEEP during anaesthesia for lung cancer surgery seems to improve postoperative outcomes. TRIALS REGISTRATION: ClinicalTrials.gov number: NCT00805077.